2017
DOI: 10.1016/j.molstruc.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

A Hirshfeld surface analysis, crystal structure and spectroscopic properties of new Zn(II) complex with N-aminoethylpiperazine ligand

Abstract: A new organic-inorganic hybrid material, 1-amonioethylpiperazine-1, 4-diium tetrachloridozincate(II) chloride, (C6H18N3)[ZnCl4]Cl, has been synthesized and characterized by various physicochemical techniques including UV-visible absorption, Infra-Red (IR), Raman and NMR spectroscopies. The compound crystallizes in the monoclinic system and P21 space group with Z = 2 and the following unit cell dimensions: a = 7.1728 (6), b = 12.4160 (11),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…the apparent lack of splitting for both 13 C peaks it is thus reasonable to assume that the signals overlap in pairs. The first resonance, at about 39 ppm can be assigned to the two CH 2 groups neighboring the protonated NH 3 + and zinc coordinated NH 2 groups (C1 and C4) [32]. The second signal at 46 ppm can be attributed the two CH 2 groups adjacent to the zinc coordinated NH group (C2 and C3) [33].…”
Section: Structure Description Of [Cdcl 2 (C 4 H 14 N 3 )]Clo 4 (2)mentioning
confidence: 99%
“…the apparent lack of splitting for both 13 C peaks it is thus reasonable to assume that the signals overlap in pairs. The first resonance, at about 39 ppm can be assigned to the two CH 2 groups neighboring the protonated NH 3 + and zinc coordinated NH 2 groups (C1 and C4) [32]. The second signal at 46 ppm can be attributed the two CH 2 groups adjacent to the zinc coordinated NH group (C2 and C3) [33].…”
Section: Structure Description Of [Cdcl 2 (C 4 H 14 N 3 )]Clo 4 (2)mentioning
confidence: 99%
“…those involving the chloride anions [H OH Á Á ÁCl (1.99), H C Á Á ÁCl (1.92) and H N Á Á ÁCl (1.73)] and the O atom of the water molecule (H N Á Á ÁO 18.19). For the special case of the enriched H C Á Á ÁZn interaction (2.48), it has been suggested that this results from the closeness of the relevant H C Á Á ÁCl interactions (El Glaoui et al, 2017). A surprising fact, however, was to find an increase in the enrichment ratio of contacts between atoms of the (ITPH 3 ) 3+ cations [CÁ Á ÁC (1.47) and CÁ Á ÁN (2.25); Table 6], compared with those of neutral free (I) [CÁ Á ÁC (1.17) and CÁ Á ÁN (0.92); Table 7], despite the former having an ab initio drawback, viz.…”
Section: Hirshfeld Surface and Enrichment Ratio (Er) Analysismentioning
confidence: 99%